Away from home. - Foo, Shu Yi. (2009)
There are 170,000 foreign domestic workers in 2006 and this number is set to increase as more families are expected to focus on their careers, and the emancipation of females. But do we really know who they are, or try to understand or get to know the life they lead? Away from Home is a radio documentary documenting the life of a maid working here in Singapore. The protagonist of this radio documentary is Rutini Murouji or Tinni, an Indonesian maid who has worked here for 9 years. It hopes to explore the issues, difficulties and sacrifices she has made but also the fun she has in Singapore while working here. Interviews with a social worker dealing with maid issues, help to expand the perspective of this radio documentary from a personal story of Tinni, to paint a bigger picture of issues faced by foreign domestic workers or FDWs here in Singapore, and what should be done. FDWs are human as well, they too have a life of their own.